2016
DOI: 10.1016/j.copbio.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the physical microenvironment on tumor progression and metastasis

Abstract: The tumor microenvironment is increasingly understood to contribute to cancer development and progression by affecting the complex interplay of genetic and epigenetic changes within the cells themselves. Moreover, recent research has highlighted that, besides biochemical cues from the microenvironment, physical cues can also greatly alter cellular behavior such as proliferation, cancer stem cell properties, and metastatic potential. Whereas initial assays have focused on basic ECM physical properties, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
358
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(379 citation statements)
references
References 72 publications
4
358
0
1
Order By: Relevance
“…[98][99][100] Additionally, YAP/TAZ is implicated in many important cancer hallmarks including proliferation, metastasis, and stem cell-like behavior. 101,102 As ovarian cancer experiences an environment with variable stiffness, the YAP/TAZ pathway is a point of interest for future mechanotransduction studies. The Rho/ Rock pathway has already been tied to stiffness effects on ovarian cancer cells 92 and it has been established as a well-known factor in both mechanotransduction and cancer progression for a variety of tumor types.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
See 1 more Smart Citation
“…[98][99][100] Additionally, YAP/TAZ is implicated in many important cancer hallmarks including proliferation, metastasis, and stem cell-like behavior. 101,102 As ovarian cancer experiences an environment with variable stiffness, the YAP/TAZ pathway is a point of interest for future mechanotransduction studies. The Rho/ Rock pathway has already been tied to stiffness effects on ovarian cancer cells 92 and it has been established as a well-known factor in both mechanotransduction and cancer progression for a variety of tumor types.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…However, the correlation that ECM stiffness has with cancer metastasis also makes it a promising avenue for new and innovative ovarian cancer treatments. As a complete examination of cancer mechanotransduction pathways is beyond the scope of this review, additional details on the influence of ECM stiffness can be found in the works by Pathak and Kumar, 87 Spill et al, 101 and Chin et al 118 …”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…on the proliferation of cancer cells. The contribution of TME is still under research and recent studies suggest that both biochemical and physical cues in the environment significantly affects the growth and development of the cancer cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that tumor cells closely interact with TME, which is constituted by blood vessels, immune cells, fibroblasts, signaling molecules, and the extracellular matrix (ECM). On one hand, tumor cells modify the microenvironment by releasing extracellular signals, thus promoting immune tolerance and neoangiogenesis, resulting in an ecosystem that is suitable for their survival; on the other hand, the now-adapted TME promotes proliferation and survival of neoplastic cells (2,3). This complex interaction between tumor cells and the surrounding environment has been the subject of several preclinical and clinical studies and has provided potential biomarkers for clinical practice as well as targets for antineoplastic therapies; this is of particular relevance, among other malignancies, in non-small cell lung cancer (NSCLC), as improvements in its management represent an urgent medical need.…”
mentioning
confidence: 99%